A note on optimal homotopy asymptotic method for the solutions of fractional order heat- and wave-like partial differential equations. (September 2015) - Sarwar, S.; Alkhalaf, Salem; Iqbal, S.; Zahid, M.A.
Abstract: Optimal homotopy asymptotic method (OHAM) is prolifically implemented to find the optimal solutions of fractional order heat- and wave-like equations. We inspect the competence of the method by examining fractional order time dependent partial differential equations. It is observed that OHAM is a prevailing and convergent method for the solutions of linear and nonlinear fractional order time dependent partial differential problems. The numerical results rendering that the applied method is explicit, effective and easy to use, for handling more general fractional order heat- and wave-like models.